Stress relaxation behavior of (Ala-Gly-Pro-Arg-Gly-Glu-4Hyp-Gly-Pro-) gelatin hydrogels under electric field: Time-electric field superposition - Tungkavet T. (2014)
An investigation has been conducted on stress relaxation functions and the corresponding relaxation time distribution functions of gelatin hydrogels for the effects of degree of crosslinking and the applied electric field strength. The experimental shift factors can be thus obtained from either the stress relaxation functions or the storage and loss moduli. Both approaches yield numerically the same shift factor values which successfully allow the time-electric field superposition of various related functions. The modified shift factors are obtained from the effective relaxation times and the material constant (Cτ). The material constant critically depends on the degree of crosslinking and weakly on the reference electric field strength used in the superposition. The relaxation time distribution clearly indicates two modes of relaxation under an electric field. The fast mode of relaxation, which occurs only under an electric field, can be attributed to the relaxation of protons present in the gelatin hydrogels.